Evidence of a higher prevalence of HPV infection in HTLV-1-infected women: a cross-sectional study - Sônia Sampaio Lôpo; Paula Matos Oliveira; Iuri Usêda Santana; Geisa Barbosa Pena; Maria Betânia Torrales; Rita Elizabeth Mascarenhas; Bernardo Galvão-Castro; Maria Fernanda Rios Grassi (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION:HTLV-1 infection increases susceptibility to other infections. Few studies have addressed the co-infection between HPV and HTLV-1 and the immune response involved in this interaction. The aim of this study was to determine the prevalence of cervical HPV infection in HTLV-1-infected women and to establish the risk factors involved in this co-infection. METHODS: A cross-sectional study was carried out in Salvador, Brazil, between September 2005 and December 2008, involving 50 HTLV-1-infected women from the HTLV Reference Center and 40 uninfected patients from gynecological clinic, both at the Bahiana School of Medicine. HPV infection was assessed using hybrid capture. HTLV-1 proviral load was quantified using real-time polymerase chain reaction (PCR). RESULTS: The mean age of HTLV-1-infected women (38 ± 10 years) was similar to that of the control group (36 ± 13 years). The prevalence of HPV infection was 44% in the HTLV-1-infected group and 22.5% in uninfected women (p = 0.03). HTLV-1-infected women had lower mean age at onset of sexual life (17 ± 3 years versus 19 ± 3 years; p = 0.03) and greater number of lifetime partners compared with the control group (4 ± 3 versus 2 ± 1; p < 0.01). In the group of HTLV-1-infected patients, there was neither difference in HTLV-1 proviral load between HPV-infected women and the uninfected. CONCLUSIONS: The prevalence of HPV infection was higher in HTLV-1-infected women. Further studies should be performed to evaluate the progression of this co-infection.